TEACHING LISTENING IN FOREIGN LANGUAGE CLASSES (Центральноазиатский журнал образования и инноваций, 2024)
A recent development in foreign language teaching methodology is the use of technology to teach communicative listening in classes. The goal is to help students become proficient speakers of a foreign language by enabling them to comprehend and perceive oral speech in a variety of communicative contexts. The abstract analyzes contemporary tools and methods for improving listening comprehension and looks at how well they work when used in conjunction with a communicative approach to teaching foreign languages. Authentic materials, interactive activities, information technology, and the teacher's role in teaching listening are just a few of the topics that will be covered in this work.